1995
DOI: 10.1002/gcc.2870120402
|View full text |Cite
|
Sign up to set email alerts
|

Interphase cytogenetics of prostatic adenocarcinoma and precursor lesions: Analysis of 25 radical prostatectomies and 17 adjacent prostatic intraepithelial neoplasias

Abstract: Twenty-five radical prostatectomy specimens were screened for the presence of numerical chromosome changes within the adenocarcinoma as well as 17 adjacent prostatic intraepithelial neoplasias (PIN) by means of interphase in situ hybridization (ISH) to routinely processed tissue sections. To this end a defined alfoid repetitive DNA probe set was used, specific for the centromeres of chromosomes 1, 7, 8, 10, 15, and Y. The cytogenetic information was correlated with histopathological and clinical features as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 33 publications
6
46
0
Order By: Relevance
“…Thus, a subset of PIN areas, irrespective of their differentiation into low-or high-grade PIN, exhibits a number of aberrations similar to invasive carcinoma. These CGH findings on PIN areas confirm for many of the chromosomal alterations earlier studies which investigated corresponding loci either with LOH (Macintosh et al, 1998;Saric et al, 1999) or FISH analysis (Alers et al, 1995;Qian et al, 1996). These data provide evidence for the biological significance of PINs and support the assumption that they represent premalignant lesions of prostate cancer.…”
Section: Tumour Progression In Prostate Cancer 205supporting
confidence: 85%
See 2 more Smart Citations
“…Thus, a subset of PIN areas, irrespective of their differentiation into low-or high-grade PIN, exhibits a number of aberrations similar to invasive carcinoma. These CGH findings on PIN areas confirm for many of the chromosomal alterations earlier studies which investigated corresponding loci either with LOH (Macintosh et al, 1998;Saric et al, 1999) or FISH analysis (Alers et al, 1995;Qian et al, 1996). These data provide evidence for the biological significance of PINs and support the assumption that they represent premalignant lesions of prostate cancer.…”
Section: Tumour Progression In Prostate Cancer 205supporting
confidence: 85%
“…At the histological level, PINs outside the invasive carcinoma are considered as premalignant lesions of prostate cancer (Bostwick and Brawer, 1987;Bonkhoff and Remberger, 1996). In the PIN-carcinoma-metastasis sequence, PIN areas are poorly characterized for chromosomal alterations because they appear as very small cell compartments which can be only studied utilizing either microdissection and subsequent molecular genetic techniques like CGH (Weber et al, 1998;Zitzelsberger et al, 1998;Kim et al, 1999) or FISH on paraffin sections (Alers et al, 1995;Qian et al, 1996;Jenkins et al, 1997). In this study, we were able to demonstrate cytogenetic changes in 5 lymph node metastases and 12 PIN areas from 6 different cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Flutamide decreased the prevalence and extent of high-grade PIN and induced epithelial atrophy. 165 There is also evidence that cessation of flutamide resulted in return of high-grade PIN. 16,166 The results of 5-alpha-reductase (finasteride) treatment in high-grade PIN are controversial and the cumulative number of cases studied is probably too small to draw firm conclusions.…”
Section: Androgen Deprivation Therapy Eliminates Pinmentioning
confidence: 99%
“…Regarding chromosome 7, 7q karyotype was found in all groups and a few of the control group also showed them. Cytogenetic study and FISH studies indicated a gain of chromosome 7 in a substantial number of prostate cancers (Alers et al, 1995;van Dekken et al, 2000), and this gain was associated with higher tumour grade, advanced pathological stage and early prostate cancer death (described as a high Gleason score) (Takahashi et al, 1995). PCR analysis of LOH on prostate cancer indicated a common focus of deletion mapping to 7q31.1-31.2 (Zenklusen et al, 1994).…”
Section: Discussionmentioning
confidence: 99%